2019
DOI: 10.1002/aur.2181
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immigrant status and signs of neurodevelopmental problems in early childhood: The French representative ELFE birth cohort

Abstract: A growing body of evidence suggests that children of immigrants may have increased risks of neurodevelopmental disorders. However, evidence based on parent report and on very young children is lacking. We therefore investigated the association between maternal immigrant status and early signs of neurodevelopmental problems in a population‐based sample of 2‐year‐old children using standardized parent‐report instruments. We used data from the French representative Étude Longitudinale Française depuis l'Enfance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
(119 reference statements)
1
6
0
1
Order By: Relevance
“…In addition to the findings of our study, evidence from Australia, Europe, Africa and North America has indicated greater risks for neurodevelopment disorders in the children of immigrant parents (Abdullahi et al, 2018;Schmengler et al, 2019). This evidence confirms the declaration by the International Society for Social Pediatrics and Child Health (ISSOP-Migration Working Group, 2018) calling for greater knowledge generation and sharing about health, education and care access risks of children of migrant parents.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to the findings of our study, evidence from Australia, Europe, Africa and North America has indicated greater risks for neurodevelopment disorders in the children of immigrant parents (Abdullahi et al, 2018;Schmengler et al, 2019). This evidence confirms the declaration by the International Society for Social Pediatrics and Child Health (ISSOP-Migration Working Group, 2018) calling for greater knowledge generation and sharing about health, education and care access risks of children of migrant parents.…”
Section: Discussionsupporting
confidence: 90%
“…Evidence indicates that migration during childhood affects neurodevelopment. Schmengler et al (2019) demonstrated the importance of the timely detection of signs of neurological abnormalities in immigrant children two years of age, given the potential repercussions for age-appropriate development.…”
Section: Introductionmentioning
confidence: 99%
“…First, ELFE is based on parents’ voluntary participation and may have left out children vulnerable to neurodevelopmental difficulties [ 9 ]. Nevertheless, the sample is heterogeneous-enough to study environmental risk factors of neurodevelopment [ 12 , 15 ] and our data were weighted to be nationally representative. Second, ELFE is a longitudinal cohort study, but the data we used are cross-sectional and we cannot rule out that children’s neurodevelopmental difficulties could influence their screen use.…”
Section: Discussionmentioning
confidence: 99%
“…Because children who use screens and those who do not are likely to different with regard to many different characteristics, covariates were controlled for using propensity scores, which were calculated based on the variables listed below [ 12 ]: Family socio-demographic characteristics reported by the mother after delivery: maternal age (< 30 vs. ≥ 30 years – the average age at first childbirth for women), paternal age (< 30 vs. ≥ 30 years), maternal and paternal birth place (France vs. Other), mother’s educational level, number of children living in the household (1, 2–3, ≥ 4), maternal and paternal residential area (Greater Paris Region; Paris and suburbs, North-West, East, West, South-West, Centre-East, and South-East) and household income per capita assessed when the child was 2 years (divided into 3 categories based on the minimum wage, average wage and above average wage in 2013, https://www.insee.fr/fr/statistiques/1375188 ) (< 1,423; 1,423–1,996; > 1,996 euros/month). Maternal mental health reported by the mother when the child was 2 months old (Edinburgh Postnatal Depression Scale (EPDS) – a score of ≥ 12 being considered as indicative of possible depression, yes vs. no [ 13 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Ces troubles résultent des difficultés rencontrées lors des phases de prémigration (expériences traumatisantes, persécutions, difficultés économiques), de périmigration (violences / discriminations, séparation et perte de réseaux sociaux), de postmigration (instabilité administrative, détention, difficultés socioéconomiques, (distance culturelle, exclusion sociale, stress) [21].…”
Section: Etat Des Connaissances Sur Les Inegalites Sociales De Santeunclassified